Fourth Generation Evaluation as a path for Knowledge Translation in mental health - Fabiane Machado Pavani; Ananda Ughini Bertoldo Pires; Christine Wetzel; Agnes Olschowsky; Maria de Lourdes Custódio Duarte (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To discuss the use of the Fourth Generation Evaluation methodology as a powerful theoretical-methodological path for the implementation of Knowledge Translation in child and adolescent mental health. Method: It comprises the description of the stages and fieldwork of a research that evaluated mental health practices aimed at adolescents in a Child and Adolescent Psychosocial Care Center, between August and December 2018, with the health care team. Results: Using strategies to involve workers in all stages, a dialectical construction of knowledge, the adaptation of the path to the field - with the implementation of interventions suggested by the participants - and the research path itself, in its condition of product/result, enable the interface with Knowledge Translation. Final considerations: The characteristics discussed allow to suggest using the Evaluation as an alternative to the implementation of Translation, especially in the field of mental health.